Where do young people live? a survey among young people in greater Kuala Lumpur / Mahazril ‘Aini Yaacob, Siti Hajar Abu Bakar and Wan Nor Azriyati Wan Abd Aziz - Yaacob, Mahazril ‘Aini; Abu Bakar, Siti Hajar; Wan Abd Aziz, Wan Nor Azriyati (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Having a decent and an appropriate home is one of the needs of the young people to progress in their lives. They, however, experienced limited housing opportunities. Majority of them could not afford to buy a home due to the price of the house, strict finance procedures, and non-inclusive housing policy practices. As an alternative, many of them are forced to rent as that is the only realistic approach to meet their financial situation. A survey was conducted with 396 young people in the Greater Kuala Lumpur (GKL), Malaysia as to examine the socio-demographic profile and current living arrangement of the young people in Malaysia. The study discovers that majority of them are non-homeowner as they are currently renting and staying with their parents. This study suggests possible strategies in response to their housing situation in order for them to have more housing opportunities.